2021
DOI: 10.1177/1471301220987386
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of masculine identity through sports-based reminiscence: An ethnographic study with community-dwelling men with dementia

Abstract: Background Despite increasing numbers of men living in isolation with dementia in the community, uptake of supportive interventions remains low. This may be because of limited availability of activities suited to men’s interests. One organisation reporting higher attendance from men is Sporting Memories, offering inclusive sports-based reminiscence and physical activities for men living with dementia. This study aimed to explore the impact of the Sporting Memories intervention on men living with dementia. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(30 citation statements)
references
References 73 publications
(84 reference statements)
0
30
0
Order By: Relevance
“…2021 33 China Effect of reminiscence therapy on spiritual wellbeing Randomized controlled trial SIWB; ULS; BRS Community dwelling volunteers Exp = 60; Ctl = 61 60-plus Exp: 28 w, 32 m; Ctl: 31 w, 30 m Sass. 2021 46 UK To determine what attending a reminiscence group meant to men living with dementia Ethnography, Participant observation; interviews 12 PwD 9 without dementia 13 spouses 12 facilitators 46 59-82 – m PwD; 60-82 – f spouse; 64-75 – other m 20 w 26 m Shellman. 2011 8 USA To explore perceived benefits and functions of reminiscence Qualitative descriptive Six focus groups and participant observations Community-dwelling older African Americans 52 Over 60 (mean 72) 90% w Shellman.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2021 33 China Effect of reminiscence therapy on spiritual wellbeing Randomized controlled trial SIWB; ULS; BRS Community dwelling volunteers Exp = 60; Ctl = 61 60-plus Exp: 28 w, 32 m; Ctl: 31 w, 30 m Sass. 2021 46 UK To determine what attending a reminiscence group meant to men living with dementia Ethnography, Participant observation; interviews 12 PwD 9 without dementia 13 spouses 12 facilitators 46 59-82 – m PwD; 60-82 – f spouse; 64-75 – other m 20 w 26 m Shellman. 2011 8 USA To explore perceived benefits and functions of reminiscence Qualitative descriptive Six focus groups and participant observations Community-dwelling older African Americans 52 Over 60 (mean 72) 90% w Shellman.…”
Section: Resultsmentioning
confidence: 99%
“…2021 33 Reminiscence discussion in combination with exercise Structured based on feedback from group To address healthy aging during covid-19 pandemic A quiet and spacious room in the community Face to face in groups Once a week for 8 weeks Members of the research team Exercise: 50–60 mins Control: 45 mins Sass. a 2021 46 Boccia, darts, table tennis, archery, discussion Structured ‘Sporting Memories’ To express masculine identity through sport Community Face to face in groups Weekly for 11 months Not stated Two hours Shellman. 2011 8 Discussion in culturally similar groups Interpersonal and Integrative reminiscence; life review To promote positive mental health and well being Senior centers and churches Face to face groups 6 one off sessions An African-American research assistant Not given Shellman.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…under the help of trained nurses [ 10 ]. Apart from the influences on cognitive impairment, over the past two decades, reminiscence therapy has also been elucidated to attenuate anxiety and depression, and improve the life quality in various cerebral diseases, including acute ischemic stroke and dementia [ 11 , 12 ]. However, few cancer patients receive reminiscence therapy, and the rare studies reported on reminiscence therapy were primarily related to colorectal and lung cancers, which show that reminiscence therapy-based care program (RTCP + UC) might relieve anxiety, depression and improve the quality of life in colorectal cancer patients and lung cancer patients [ 13 , 14 ], while no report suggests the same finding in the surgical prostate cancer.…”
Section: Introductionmentioning
confidence: 99%